Istanbul Appearances : Beauty and the Making of Middle-Class Femininities in Urban Turkey - Liebelt, Claudia (Book collections on Project MUSE., 2022)
"Using ethnographic fieldwork carried out in beauty salons and clinics in different parts of Istanbul between 2011 and 2015, the manuscript argues that the study of embodied beauty offers unique insights into the gender dynamics and the politics of social and political reproduction amidst the recent conservative-authoritarian turn in Turkey"--